Gascón Inchausti, F., Hess, B. (eds.), The Future of the European Law of Civil Procedure. Cordination or Harmonisation? - Schumann Barragán, Guillermo (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Este artículo reseña: Gascón Inchausti, F., Hess, B. (eds.), The Future of the European Law of Civil Procedure. Cordination or Harmonisation?, Intersentia, Cambridge, 2020, 290 pp.